The Relationship between Third Trimester Placental Thickness Measured Ultrasonographically and Pregnancy Outcome - حسن, لؤي (Latakia University Journal -Medical Sciences Series, 2021)
Background: Placenta is the connecting organ between the mother and the fetus. The sonographic assessment of placenta can give information about the nutritional status of the fetus. There are very few studies correlating placental thickness with pregnancy outcome. Aim: To correlate ultrasonographic placental thickness at ≥ 37 weeks pregnancy with neonatal outcome. Materials and Methods: This was a prospective observational longitudinal study conducted at Obstetrics and Gynecology Department, Tishreen University Hospital, Lattakia, Syria, during the period between August 2019 – August 2020. The study enrolled 385 women with uncomplicated singleton pregnancies at term gestation (37 weeks or more). Placental thickness was measured by ultrasound. Placental thickness was categorized as normal (10th–95th percentile), thin (< 10th percentile) and thick (> 95th percentile) and was correlated with birth weight and neonatal outcome. Results: There was a significant positive correlation between placental thickness and birth weight in the third trimester (r=0.697, p<0.0001). Neonatal outcome was good in women with normal placental thickness (10th–95th percentile) and was compromised in women with thin (< 10th percentile) and thick (> 95th percentile) placentae. Conclusion: Placental thickness at ≥ 37 weeks is correlated well with the birth weight and is a good prognostic factor in assessing neonatal outcome. Therefore, placental thickness should be measured in addition to biometric parameters in antenatal women undergoing ultrasound.